Pengembangan Multimedia Interaktif Berbasis Articulate Storyline Materi Penerapan Nilai-nilai Pancasila - Andriyan Nur Pratama; Hamdan Husein Batubara (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2021)
The development of interactive media based on articulate storylines for practicality and ease of use of civic education learning is a significant thing to review, especially material on the application of Pancasila in everyday life. This research is subject to elementary school teachers using the Research and Development (R&D) research method using the ADDIE development model (Analysis, Design, Development or Production, Implementation or Delivery and Evaluations). The feasibility of this media is carried out through media expert tests and material expert tests. While the practicality of this media by conducting a limited trial involving 5 teachers who were then given a questionnaire, to find out the teacher's response to the interactive media based on the articulated storyline that was developed. Articulate storyline-based interactive media is proven to be good. This is proven by the percentage results that reach 70% for the media expert test to get the Good category. The results of the Material expert test get a percentage result of 80 in good category, so that from the media expert test and material expert test the average percentage is 75%, where the media is in good category and interactive media based on articulate storylines is proven to be practical. This is proven based on the results of the questionnaire responses from elementary school teachers, with the percentage results reaching 90.3%.